593 Squamous Cell Carcinoma in Renal Pelvis of a Fused Pelvic Kidney; Case Report and Literature Review. (19th August 2022) - Ilangovan, S; Neves, J; Bex, A; Tran, M
Abstract: This case report details a rare case of squamous cell carcinoma present in the renal pelvis of a fused pelvic kidney, a congenital complete renal fusion anomaly. A 52-year-old man with no previous urological history presented with intermittent haematuria and weight loss. He was found to have a large complex mass (14.3 cm×4.5 cm×15.5 cm) in the right moiety of a pelvic fused kidney on CT and subsequently underwent an open hemi-nephrectomy. He recovered well following surgery, however, unfortunately developed rapid recurrence, and died from disease progression after 6 months. This report demonstrates the use of 3D anatomical reconstruction to help pre-operative planning of complex surgical cases. We also include histological analysis of the tumour in detail. This case report emphasises that squamous cell carcinoma can occur due to precipitating factors such as renal calculi or infection, which are more prevalent in fusion anomalies of the kidney. Although a rare malignancy, this tumour type is associated with an aggressive behaviour and poor prognosis.